Insights into recent findings and therapeutic potential of nonhistone lactylation in cancer - Jia, Jing; Liu, Na; Zhu, Xiaoren; Chen, Minbin (Frontiers in Molecular Biosciences, 2025)
Lactylation, a recently identified post-translational modification, has become a crucial regulatory mechanism beyond its conventional metabolic role. Unlike histone lactylation, which regulates gene expression, nonhistone lactylation directly acts on effector proteins involved in processes such as signal transduction, metabolic reprogramming, and DNA damage repair. This article systematically reviews how nonhistone lactylation regulates biological processes related to cancer via mechanisms such as modulating protein interactions, stability, subcellular localization, and enzymatic activity. In addition, it comprehensively examines the potential applications and challenges in targeting nonhistone lactylation modification in antitumor treatment.